Deoxygenation of chalcogen oxides EO2 (E = S, Se) with phospha-Wittig reagents. Issue 48 (30th November 2022) - Dankert, Fabian; Gupta, Priyanka; Wellnitz, Tim; Baumann, Wolfgang; Hering-Junghans, Christian
Abstract : A transfer of EO2 (E = S, Se) into different phosphorus heterocycles in a metal-free manner is established using phospha-Wittig reagents. Abstract : In here we present the deoxygenation of the chalcogen oxides EO2 (E = S, Se) with R-P(PMe3 ), so-called phospha-Wittig reagents. The reaction of DABSO (DABCO·2SO2 ) with R-P(PMe3 ) (R = Mes*, 2, 4, 6- t Bu3 -C6 H2 ; Mes Ter, 2, 6-(2, 4, 6-Me3 -C6 H2 )2 -C6 H3 ) resulted in the formation of thiadiphosphiranes (RP)2 S (1:R ), while selenadiphosphiranes (RP)2 Se (2:R ) were afforded with SeO2, both accompanied by the formation of OPMe3 . Utilizing the sterically more encumbered Dip Ter-P(PMe3 ) ( Dip Ter = 2, 6-(2, 6-iPr2 -C6 H3 )2 -C6 H3 ) a different selectivity was observed and ( Dip TerP)2 Se (2: Dip Ter ) along with [Se(μ-P Dip Ter)]2 (3: Dip Ter ) were isolated as the Se-containing species in the reaction with SeO2 . Interestingly, the reaction with DABSO (or with equimolar ratios of SeO2 at elevated temperatures) gave rise to the formation of the OPMe3 -stabilized dioxophosphorane (phosphinidene dioxide) Dip TerP(O)2 -OPMe3 (4: Dip Ter ) as the main product. This contrasting reactivity can be rationalized by two potential pathways in the reaction with EO2 : (i) a Wittig-type pathway and (ii) a pathway involving oxygenation of the phospha-Wittig reagents and release of SO. Thus, phospha-Wittig reagents are shown to be useful synthetic tools for the metal-free deoxygenation of EO2 (E = S, Se).